Potentiation of DNA adduct formation in HL-60 cells by combinations of benzene metabolites. - Lévay, G (1992)
Using P1 nuclease enhanced 32P postlabeling, we investigated DNA adduct formation in HL-60 promyelocytic leukemia cells treated with the benzene metabolites hydroquinone, catechol, and 1,2,4-benzenetriol. Comparison of the slopes of the dose-response curves showed that hydroquinone was 7-9 times more effective than 1,2,4,-benzenetriol and catechol at inducing DNA adducts. Comparison of hydroquinone with catechol showed a good correlation between adduct formation and cytotoxicity. Similar comparisons of hydroquinone and 1,2,4,-benzenetriol suggest that cellular processes in addition to DNA adduct formation contributed to cytotoxicity. In cells treated with the combination of hydroquinone and either catechol or 1,2,4,-benzenetriol, DNA adduct formation was 3-6 times greater than the sum of adduct formation produced by single-agent treatments. Treatment with hydroquinone and 1,2,4,-benzenetriol produced DNA adducts not detected after treatment with either metabolite alone. The synergistic interaction of benzene metabolites in the production of DNA adducts may play an important role in the genotoxic effects of benzene in vivo.